Nursing in the context of COVID-19: systematic mapping (Research, Society and Development, 2021)
Introduction: The nursing work is in the front line in the fight against COVID-19. This class of workers is essential for the functioning of all health systems, since despite all the difficulties faced, related to the profession and the existing pressure due to the epidemiological crisis experienced, it still contributes to science with its scientific production. Objective: To identify in the scientific production of nursing on the theme of COVID-19. Methods: This is a study of the literature that aims to map in a systematic manner the scientific production of nursing in the context of COVID-19. The systematic mappings consist of a tool that enables an enlarged view of the evidence base structure facing a research question. In this way, the research question will be: What is the scientific production of nursing on the theme of COVID-19? A search strategy for studies will be drawn up through the determination of the best descriptors and/or keywords that may be related to the theme. Worldwide reference databases will be considered for greater range of search. The searches will be carried out in a specified period, in which all publications will be accessed, without any restrictions on the timeline. For the selection of studies, a careful reading of the title, abstract and keywords and subsequently the adequacy to the inclusion and exclusion criteria established will be carried out. The evidence found will be presented in a narrative manner, through tables, diagram and thematic map to be elaborated in the software Arcgis.